Comparison of physical interventions, behavioral interventions, natural health products, and pharmacologics to manage hot flashes in patients with breast or prostate cancer: protocol for a systematic review incorporating network meta-analyses - Hutton, Brian; Yazdi, Fatemeh; Bordeleau, Louise; Morgan, Scott; Cameron, Chris; Kanji, Salmaan; Fergusson, Dean; Tricco, Andrea; Straus, Sharon; Skidmore, Becky; Hersi, Mona; Pratt, Misty; et al. (Université d'Ottawa | University of Ottawa, 2015)
Abstract Background Breast and prostate cancers are the most commonly diagnosed non-dermatologic malignancies in Canada. Agents including endocrine therapies (e.g., aromatase inhibitors, gonadotrophin-releasing hormone analogs, anti-androgens, tamoxifen) and chemotherapy have improved survival for both conditions. As endocrine manipulation is a mainstay of treatment, it is not surprising that hot flashes are a common and troublesome adverse effect. Hot flashes can cause chills, night sweats, anxiety, and insomnia, lessening patients’ quality of life. These symptoms impact treatment adherence, worsening prognosis. While short-term estrogen replacement therapy is frequently used to manage hot flashes in healthy menopausal women, its use is contraindicated in breast cancer. Similarly, testosterone replacement therapy is contraindicated in prostate cancer. It is therefore not surprising that non-hormonal pharmacological treatments (anti-depressants, anti-epilectics, anti-hypertensives), physical/behavioral treatments (e.g., acupuncture, yoga/exercise, relaxation techniques, cognitive behavioral therapy), and natural health products (e.g., black cohosh, flax, vitamin E, ginseng) have been studied for control of hot flashes. There is a need to identify which interventions minimize the frequency and severity of hot flashes and their impact on quality of life. This systematic review and network meta-analysis of randomized studies will synthesize available evidence addressing this knowledge gap. Methods/design An electronic search of Medline, Embase, AMED, PsycINFO, and the Cochrane Register of Controlled Trials has been designed by an information specialist and peer reviewed by a second information specialist. Study selection and data collection will be performed by two reviewers independently. Risk of bias assessments will be completed using the Cochrane Risk of Bias Scale. Outcomes of interest will include validated measures of hot flash severity, hot flash frequency, quality of life, and harms. Bayesian network meta-analyses will be performed where judged appropriate based on review of clinical and methodologic features of included studies. Discussion Our review will include a broad range of interventions that patients with breast and prostate cancer have attempted to use to manage hot flashes. Our work will establish the extent of evidence underlying these interventions and will employ an inclusive approach to analysis to inform comparisons between them. Our findings will be shared with Cancer Care Ontario for consideration in the development of guidance related to supportive care in these patients. Systematic review registration PROSPERO: CRD42015024286